Minichromosome maintenance complex is a critical node in the miR-183 signaling network of MYCN-amplified neuroblastoma cells - Lodrini, Marco; Witt, Olaf; Deubzer, Hedwig (Journal of proteome research, 2016)
MYCN and HDAC2 jointly repress the transcription of tumor suppressive miR-183 in neuroblastoma. Enforced miR-183 expression induces neuroblastoma cell death and inhibits xenograft growth in mice. Here we aimed to focus more closely on the miR-183 signaling network using a label-free mass spectrometric approach. Analysis of neuroblastoma cells transfected with either control or miR-183 expression vectors identified 85 differentially expressed proteins. All six members of the minichromosome maintenance (MCM) complex, which is indispensable for initiation and elongation during DNA replication and transcriptionally activated by MYCN in neuroblastoma, emerged to be down-regulated by miR-183. Subsequent annotation category enrichment analysis revealed a ∼14-fold enrichment in the “MCM” protein module category, which highlighted this complex as a critical node in the miR-183 signaling network. Down-regulation was confirmed by Western blotting. MCMs 2-5 were predicted by in silico methods as direct miR-183 targets. Dual-luciferase reporter gene assays with 3′-UTR constructs of the randomly selected MCMs 3 and 5 experimentally confirmed them as direct targets of miR-183. Our results reveal the MCM complex to be a critical and directly regulated node within the miR-183 signaling network in MYCN-amplified neuroblastoma cells.